Low birth weight: an observational study of maternal and neonatal factors in a rural tertiary care hospital, Telangana, India - Nabhi, Murty V. R.; S., Ramjyoti; B., Vydehi; K., Vasantha; Gillella, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Poor maternal health among Indian women is of global significance because India is home to 1/5th of the world’s births. 27% of these newborn babies in India are low birth weight (LBW), an important cause of high infant mortality. This study was conducted among puerperal women who delivered LBW babies in our hospital to know the various factors pertaining to socio-demographic, obstetric and anthropometric characteristics. Methods: this observational study was conducted in the department of obstetrics and gynecology at Bhaskar medical college and hospital, Moinabad, Hyderabad from January 2016 to June 2017. The study sample were those who delivered LBW babies in our hospital and a set questionnaire was used to collect the relevant details. Results: 75% of these mothers were in the age group of 20-25 years, 73.5% had more than 10 years of schooling. About 64% of these women had their 1st antenatal visit in 1st trimester of pregnancy and 54% had their 1st ultrasound in 1st trimester. 36 babies had NICU admission, either at our hospital or at a level III NICU facility, and all had good neonatal outcome. Conclusions: The state must endeavor to make quality health free and easily accessible to pregnant women so that all can avail these services to better the maternal and neonatal outcomes. This will be helpful in improving the overall health of our population over the next few decades.